Age-related proprioceptive decline is not seen in lifelong skiing and snowboarding participants: Lessons for balanced active healthy ageing - Tracey J. Dickson; Jeremy Witchalls; F. Anne Terwiel; Gordon Waddington; Rachel Jaros (Elsevier, 2022)
Objectives: Ankle proprioception is important for effective human movement and thus active healthy aging. Chronic ankle instability (CAI) may be a contributing factor in proprioception decline. Proprioception and aging research indicate that there is age-related decline in proprioception, however, most research has been on activities conducted in flat, even, and unchanging environments. Thus, to support active healthy aging theory and practice across diverse real-world environments this research explores snowsports activities that are conducted in more dynamic environments and that may be participated in across the lifespan. Design: This research used a cohort comparison approach to study whether regular snowsport participation (i.e., skiing and snowboarding) is correlated with i) age-related proprioception decline, and ii) proprioception deficits observed with CAI. Methods: 142 advanced and elite snowsport participants (age-range 12-70 years), were recruited over a two-year period. Participants completed a questionnaire that included: prior snowsport experience, ankle injury history and the Identification of Functional Ankle Instability scale (IdFAI). Lower limb proprioception was tested using the Active Movement Extent Discrimination Assessment (AMEDA) device. Results: There were no significant differences in AMEDA scores between i) age categories; ii) those with or without CAI; nor iii) between females and males. Conclusions: These results show that regular snowsport participation such as skiing and snowboarding, that occur in dynamic and changing environments, may i) protect against age-related proprioception decline, and ii) provide a rehabilitative effect for CAI. Thus, snowsport participation may be beneficial for active healthy aging and fall prevention.